PERUMUSAN STRATEGI UNTUK MENINGKATKAN KEPUASAN PASIEN RAWAT JALAN INSTALASI FARMASI RUMAH SAKIT JASA KARTINI TASIKMALAYA DENGAN ANALISIS SWOT - , Githa Fungie Galistiani; , Prof. Dr. Lukman Hakim, M.Sc., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Quality of service provided hospitals closely related to the quality of services Hospital Pharmacy Department (IFRS). IFRS as a service unit that provides health services in hospitals are required to always be able to provide a quality service, fast, fun and satisfying customers. IFRS will seek to transform and to meet patient needs for patients are satisfied with the services provided. Therefore, this study was conducted in order to plan strategies that then can determine alternative strategies in an effort to improve patient satisfaction in accordance with the internal-external environmental conditions of IFRS Jasa Kartini Tasikmalaya. This research is a non-experimental design, type a qualitative descriptive. Data collected in the form of qualitative data conducted with in-depth interview on the subject of research, then as supporting data was also investigated quantitatively using a questionnaire to determine patient satisfaction with outpatient care, morale scale conditions and employee satisfaction of IFRS Jasa Kartini Tasikmalaya. Information collected, compiled, and then analyzed using analysis of Strenghts-Weaknesses-Opportunities-Threats (SWOT). The analysis results were used as the basis for the formulation of strategic factors, which then performed the analysis using the Quantitative Strategic Planning Matrix (QSPM) as a tool of decision-making strategies. Result of service quality gap analysis Pharmacy Department of Jasa Kartini Hospital Tasikmalaya to five dimensions is the responsiveness (-0.61)